Side-detecting optical fiber coated with Zn(OH)2 nanorods for ultraviolet sensing applications. (21st August 2017) - Azad, S; Parvizi, R; Sadeghi, E
Abstract: This paper presents an improved coupling efficiency and side detecting of UV radiation induced by light scattering and luminescent features of Zn(OH)2 nanorods coated multimode optical fibers. Uniform and high density Zn(OH)2 nanorods were grown hydrothermally on the core of chemically etched multimode optical fibers. The prepared samples were characterized through x-ray diffraction patterns, scanning electron microscopy and photoluminescence spectroscopy. The detecting technique was based on the intensity modulation of the side coupled light through the Zn(OH)2 nanorods. A simple and cost-effective UV radiation detecting setup has been designed. Experimentally estimated coupling efficiency of the proposed setup was obtained near 11%. The proposed device exhibited stable and reversible responses with a fast rising and decaying time of about 1.4 s and 0.85 s, respectively.